Pengembangan Media Pembelajaran Berbasis Canva untuk Meningkatkan Minat dan Hasil Belajar Pendidikan Agama Buddha - Sella Selviana (Dhammavicaya : Jurnal Pengkajian Dhamma, 2025)
This research is motivated by the low interest in learning among students. The application of learning media in the form of videos is one alternative to overcome this problem. This study aims to produce learning media in the form of videos made using the Canva application and analyze its influence on the interests and learning outcomes of students in the subject of Buddhist Religious Education and Character Education for grade V elementary schools with the material Emulating Bodhisattva and Buddha, lesson 17. This development uses the ADDIE development model (Analysis, Design, Development, implementation and evaluation). The research instruments used were interview sheets and questionnaires. The feasibility of the learning video was validated by media experts and material experts and tested on grade V students of SDS Keluarga Universal Tanjungpandan. The results of the media expert validation obtained results of 60 (good) and 70 (very good) and the results of the material expert validation obtained results of 85 (Very good). In addition, the teacher assessment score obtained was 65 which has a good validation level. The results of the responses of grade V students of SDS Keluarga Universal obtained a percentage of 84.4% (very good). The results of the t-test showed that there was a significant difference between the group using the learning video and the control group. Based on the results of the study, it was concluded that the learning video had an effect on increasing the interest and learning outcomes of class V students of SDS Keluarga Universal Tanjungpandan.